How the Structure of GDP of Ukraine Responded to COVID-19 - Motoryn, R. М.; Motoryna, Т. М.; Prykhodko, К. R. (Statistics of Ukraine, 2021)
The impact of the COVID-19 pandemic on the structure of Ukrainian GDP is studied, with summing up the causes of impact occurrence and mechanisms of manifestation. The peculiarities of the pandemic’s impact on the institutional and industrial structure of economy in the specific conditions of Ukraine are revealed. The dynamics of the structure of the domestic GDP in the conditions of pandemic is analyzed. The contribution of the sectors of non-financial corporations, households, financial corporations and government in the Ukrainian GDP is highlighted. It is shown that the increased economic activity of non-financial sector resulted in a growth in dividends, royalties and other components of the property income. However, financial corporations, general government and households were losing property incomes, first of all due to the decreased interest rate of the National Bank of Ukraine, which reduced incomes of financial corporations in form of interests on loans, bond yields of the government, and deposit incomes of households. Problems of redistribution of primary incomes of sectors by the financial system are discussed. Emphasis is made on the banking sector. With the pandemic shattering the financial health of banks, they started to increase the commission fees to compensate the losses. This process is expected to go on in the forthcoming months. At the initial period of the economy freezing, banks did not feel its outcomes as severely as sectors like tourism, transport or culture. The dynamics of GDP structure by economic activity is analyzed by three dimensions given the available national accounts data of the State Statistics Service of Ukraine. The analysis covers, first, the dynamics of GDP structure by economic activity in absolute terms, second, the dynamics of GDP structure in current prices, and, third, the dynamics of GDP structure in last year prices, thus eliminating the price effect for the dynamics of GDP. The adverse impact of the dynamics of prices occurred in the following sectors: manufacturing; health care and social aid; education; water supply, sanitation, waste treatment; transport; storage facilities; postal and courier activities; temporary accommodation and public catering. While the grown prices for these sectors’ products increased their weight in GDP in current prices, this weight was smaller in comparable prices. The study was conducted on the basis of research publications and material of the State Statistics Service of Ukraine and professional organizations. Desk research method was used in the process, i. e. analysis of available data, involving extraction and exploration of the already available information, which is the basis for producing new data in line of the author’s research objective.